บรรยากาศองค์การ ความสอดคล้องระหว่างบุคคลกับงาน และความผูกพันในงานของพนักงานเจนวาย : การวิจัยผสานวิธี - ชลลดา อรุณสันติโรจน์ (จุฬาลงกรณ์มหาวิทยาลัย, 2014)
The purpose of this research is to examine relationship between organizational climate, person-job fit, and work engagement among generation-y employees by using a concurrent triangulation mixed methods research. Participants were 120 gen-y employees in the Bangkok metropolis completed questionnaire, and 6 gen-y employees were interviewed. The instruments were The Climate Questionnaire, Person-Environment Fit Scales, Work Engagement Scales, and an interview protocol. Findings were as follows (1) 5 out of 6 dimensions of organizational climates; standard, responsibility, recognition, support, and commitment were positively correlated with work engagement which is significantly different from zero at alpha level .01 (2) 2 dimensions of person-job fit; demand-ability job fit and need-supplies job fit were positively correlated with work engagement which is significantly different from zero at alpha level .01 (3) 6 dimensions of organizational climates and 2 dimensions of person-job fit predicted work engagement at 46 percent which is significantly different from zero at alpha level .01, which need-supplies job fit is the best predictor in this sudy. Finding from qualitative analysis supported the quantitative finding that gen-y employees who has a high work engagement perceived high standard of work, be freely responsible for work, have a good co-workers, be proud of own work, and be the part of organization, including perceived that their ability fit a job demand and a job satisfies their needs.These factors make gen-y employees engaged with a work and keep employees to continuing working without turn over.